PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN NEARPOD TERHADAP AKTIVITAS BELAJAR GEOGRAFI KELAS X DI SMA NEGERI 1 GUNUNG TALANG - Pernando, Jefri; Surtani, Surtani (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
This study aims to determine the effect of using Nearpod interactive learning media on student learning activities in the class X Geography subject at SMA Negeri 1 Gunung Talang. The type of research applied is quantitative with a correlational approach. Sampling using total sampling obtained 88 respondents from class X IPS 1, X IPS 2, and X IPS 3. The data collection technique used the help of a questionnaire for Nearpod media and student learning activities. The results of this study conclude: 1) The use of Nearpod media and learning activities is classified as moderate with the percentages of 61% and 58%, respectively. 2) The use of Nearpod media has a significant effect on student learning activities. This is evidenced by the results of the analysis where r count (0.577) is greater than r table at a significant level of 5% or 1%, namely 0.209 < 0.577 > 0.273, so H0 rejected and H1 accepted. The influence of Nearpod media has a significant effect on student learning activities of 33.2%. This is evidenced by the correlation coefficient (r) of 0.577 and the value of the coefficient of determination (r2)of 0.736. This means that Nearpod is able to contribute 33.2% to learning activities. student. Looking at the regression equation = 41.553 + 0.506 X shows that every time there is an additional value on Nearpod media by 1, it increases the value of learning activities by 0.506.